PELATIHAN DESAIN MEREK SEBAGAI SARANA MEMPERKUAT IDENTITAS PRODUK - Agus Frianto; Monika Tiarawati; Nadia Asandimitra; Yessy Artanti; Widyastuti Widyastuti (Universitas Ahmad Dahlan, Yogyakarta, 2019)
Trademark as an activity to make a name, symbol or identity to distinguish one product/service from another product/service. Therefore, entrepreneurs/business owners/startup founders need to consider how brands are for products/services that they want to sell. With a brand, the total value of the product is higher so that consumers can see the brand as an important part of the product. Consumers will more easily differentiate company products from competitors through brands. However, the importance of giving brand to the product was not realized by SMEs who were in Ngawen and Randuboto Villages, Sidayu District, Gresik Regency. Their only focus is product sales. Brands can be a long-term investment for business owners. Brands that are well managed by business owners will provide long-term benefits. The purpose of this outreach program is to provide training on how to make a good brand so that it can be easily recognized by the general public. The outputs of this outreach program activity are brand designs that are ready to be printed and pasted on the product packaging of business actors. The results of this outreach program activity show that several business actors have been able to create attractive brands so that they can be easily recognized by consumers and ultimately create an identity for SME products in Sidayu District, Gresik